AGRITECH: INVESTOR HOPE OR MARKET ILLUSION? - Dodit Efendi; Herlinda Maya kumalasari (International Journal of Economic Integration and Regional Competitiveness, 2026)
Objective: This study is motivated by the inconsistency between positive market sentiment regarding agritech technology collaboration and the declining movement of stock prices. The purpose of this study is to analyze the effect of Return on Assets (ROA), Debt to Assets Ratio (DAR), and Current Ratio (CR) on stock prices of agritech sector companies. Method: This research employs a quantitative method using panel data regression analysis. The data used are secondary data obtained from agritech companies listed on the Indonesia Stock Exchange during the 2022–2025 period, selected through a purposive sampling technique. The analysis was conducted using EViews 12 with the Random Effect Model (REM). Results: The results indicate that ROA and DAR have a positive and significant effect on stock prices, while CR has a negative and significant effect. Simultaneously, all independent variables significantly influence stock prices. Novelty: These findings suggest that investors tend to prioritize profitability and financing strategies over liquidity in making investment decisions. Therefore, not all financial ratios are equally responded to by the market in determining stock prices in the agritech sector.